2015
DOI: 10.1117/12.2176853
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography, ultrasound C-scan and microscope for non-destructive and destructive evaluation of 3D carbon fiber materials: a comparative study

Abstract: 3D Carbon fiber polymer matrix composites (3D CF PMCs) are increasingly used for aircraft construction due to their exceptional stiffness and strength-to-mass ratios. However, defects are common in the 3D combining areas and are challenging to inspect. In this paper, Stitching is used to decrease these defects, but causes some new types of defects. Infrared NDT (non-destructive testing) and ultrasound NDT are used. In particular, a micro-laser line thermography technique (micro-LLT) and a micro-laser spot ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…However, these techniques cannot detect submillimeter porosity because the distance between the specimen and the camera is usually small (approximately 4.5 cm) when using a microlens, which is difficult for the experimental configurations. Flying spot laser thermography used to detect the subsurface submillimeter flaws in previous composites work was reported [1,2]. However, the results revealed that the technique cannot work on micro-sized flaws.…”
Section: Introductionmentioning
confidence: 38%
See 3 more Smart Citations
“…However, these techniques cannot detect submillimeter porosity because the distance between the specimen and the camera is usually small (approximately 4.5 cm) when using a microlens, which is difficult for the experimental configurations. Flying spot laser thermography used to detect the subsurface submillimeter flaws in previous composites work was reported [1,2]. However, the results revealed that the technique cannot work on micro-sized flaws.…”
Section: Introductionmentioning
confidence: 38%
“…The authors proposed micro-laser line thermography (pulsed micro-LLT) [1], which was verified to work for subsurface submillimeter flaws in composites [2]. In this article, pulsed micro-LLT was used to detect the subsurface submillimeter porosities in a 3D preformed CFRP specimen for the evaluation of detection capabilities.…”
Section: B Pulsed Micro-laser Line Thermographymentioning
confidence: 99%
See 2 more Smart Citations
“…1 However, it may cause new types of flaws, especially submillimeter flaws. 2,3 Microscopic inspection is the most often used technique for identifying the submillimeter flaws, but it is timeconsuming and destructive. 2,3 Therefore, nondestructive testing (NDT) of materials is significant and increasingly used nowadays.…”
Section: Introductionmentioning
confidence: 99%